Plagiarism as a Moral Crisis in Students: A Normative Ethical Approach - Fajar Ahmad; Nandana Kafii Anantara; Ulfita Mardhatillah; Ika Triayu Rahmadiah; Muhammad Oktorama Setiawan (ISNU Sumatera Utara, 2025)
Plagiarism in academia is a serious violation of ethics and scientific integrity, particularly among students. This phenomenon reflects a moral crisis that not only impacts individual quality but also threatens academic culture as a whole. This study aims to examine plagiarism behavior from a normative ethics perspective, emphasizing the approaches of deontology, utilitarianism, and virtue ethics. The method used is a literature study, by analyzing various relevant literature related to academic ethics and morality in higher education. The results of the analysis indicate that plagiarism is not only a form of intellectual dishonesty but also reflects students' weak moral awareness in understanding academic responsibility. The deontological approach views plagiarism as a violation of moral obligations, utilitarianism views it as an act that harms the academic community as a whole, while virtue ethics emphasizes the importance of developing honest and responsible character in individuals. Based on these findings, this study concludes that overcoming plagiarism cannot be done solely through sanctions, but requires a comprehensive and continuous approach to academic ethics education. Education that instills the values of honesty, integrity, and moral responsibility from an early age is key to building a healthy and dignified academic culture.